2020
DOI: 10.21547/jss.731980
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 (Koronavirüs)’un Borsa İstanbul Sektör Endeks Getirileri Üzerindeki Etkisi: Bir Olay Çalışması

Abstract: Bu çalışma COVID-19 salgınının Borsa İstanbul sektör endeks getirileri üzerindeki etkisini analiz etmeyi amaçlamaktadır. COVID-19 ilk olarak 2019 yılı aralık ayında Çin'in Wuhan kentinde ortaya çıkmış olup kısa sürede pek çok ülkeye yayılmıştır. Dünya Sağlık Örgütü tarafından pandemi ilan edilmesi ile gerek ulusal gerekse uluslararası düzeyde ticari ve mali hareketlilikler kısıtlanmıştır. Bu durum hem finansal hem de reel sektörü doğrudan etkilemiştir. Dünyada daha önce yaşanan salgınların ülke ekonomileri üze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 22 publications
3
10
1
Order By: Relevance
“…So far, studies investigating the impact of COVID-19 on Borsa Istanbul have generally used event study method. They reveal that the number of cases and the announcement of social measures have negatively affected the returns (Keles 2020), and the returns of sectors such as tourism, transportation, textile are more affected (Keles, 2020;Kilic, 2020, Kandil-Göker, Eren & Karaca, 2020. To the best of our knowledge, this study is the first to analyze the impact of COVID-19-related news on Borsa Istanbul using quantile regression analysis.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…So far, studies investigating the impact of COVID-19 on Borsa Istanbul have generally used event study method. They reveal that the number of cases and the announcement of social measures have negatively affected the returns (Keles 2020), and the returns of sectors such as tourism, transportation, textile are more affected (Keles, 2020;Kilic, 2020, Kandil-Göker, Eren & Karaca, 2020. To the best of our knowledge, this study is the first to analyze the impact of COVID-19-related news on Borsa Istanbul using quantile regression analysis.…”
Section: Introductionmentioning
confidence: 90%
“…Considering the studies related to Turkish financial markets, the impact of COVID-19 have been analyzed on financial reporting (Cavlak, 2020), stock market returns (Coban, Coşkun, & Coban, 2020;Kandil et al, 2020;Kayral & Tandogan, 2020;Keleş, 2020;Kılıc, 2020;Özkan, 2020), CDS spreads (Kartal, 2020), food and beverage sectors (Levent, 2020), and tourism sector (Korkut et al,2020;Kandil-Göker, Eren & Karkaca, 2020) have been analyzed so far.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wu and Olson (2020) divided the pandemic's impact into short-term, long-term, and systematic risks. Kandil Göker et al (2020), in their event study, examined the pandemic effects on 26 Borsa Istanbul sector indices and found that the CAARs of only the banking sector and three other sectors were positive; however, the returns of the banking sector were insignificant. Phuong (2021) examined the COVID-19 impacts on the Vietnamese banking sector stocks using the event study method around three lockdown events and found that the lockdowns positively impacted the banking sector stock returns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are also studies in the literature examining the impact of the Covid-19 pandemic on Turkish financial markets (Kandil Göker et al, 2020;Öztürk et al, 2020;Tayar et al, 2020;Kılıç, 2020;Özdemir, 2020;Korkut et al, 2020). Kandil Goker et al (2020 found that the highest decreases in the Covid-19 period were in the Sports, Tourism and Transport indices.…”
Section: Article In Press -Corrected Proofmentioning
confidence: 99%